2020
DOI: 10.1073/pnas.1915152117
|View full text |Cite
|
Sign up to set email alerts
|

A molecularly engineered antiviral banana lectin inhibits fusion and is efficacious against influenza virus infection in vivo

Abstract: There is a strong need for a new broad-spectrum antiinfluenza therapeutic, as vaccination and existing treatments are only moderately effective. We previously engineered a lectin, H84T banana lectin (H84T), to retain broad-spectrum activity against multiple influenza strains, including pandemic and avian, while largely eliminating the potentially harmful mitogenicity of the parent compound. The amino acid mutation at position 84 from histidine to threonine minimizes the mitogenicity of the wild-type lectin whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 61 publications
6
79
0
1
Order By: Relevance
“…(Lusvarghi and Bewley, 2016) against HIV and influenza infection, the latter of which has recently entered clinical trials (National Institutes of Health, 2019), certainly provides an interesting precedent for adaptation of these lectins for pharmaceutical application. In this regard, a recent report describes an engineered Banlec that exhibits anti-influenza activity in mice and is extremely well tolerated (Cové s-Datson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(Lusvarghi and Bewley, 2016) against HIV and influenza infection, the latter of which has recently entered clinical trials (National Institutes of Health, 2019), certainly provides an interesting precedent for adaptation of these lectins for pharmaceutical application. In this regard, a recent report describes an engineered Banlec that exhibits anti-influenza activity in mice and is extremely well tolerated (Cové s-Datson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Tseng at. al, developed the hACE2 Tg mouse lineages (i.e., AC-12, AC-22, AC-50, AC-63, and AC-70) expressing hACE2 under the CAG promoter, a composite promoter consisting of the cytomegalovirus immediate early enhancer, the chicken β-actin promoter, rabbit globulin splicing, and polyadenylation sites to drive high levels of gene expression in eukaryotic expression Mortality (%) The viral dosage used in the study, 2.3 × 10 4 plaque-forming units (PFU), was converted to the estimated TCID50 by the conversion TCID50 ≈ 0.7 PFU [71].…”
Section: Ac70 Ac22 and Ac63 Hace2 Tg Mouse Modelsmentioning
confidence: 99%
“…The viral dosage used in the study, 10 5 PFU, was converted to the estimated TCID50 by the conversion TCID50 ≈ 0.7 PFU [71].…”
Section: Ac70 Ac22 and Ac63 Hace2 Tg Mouse Modelsmentioning
confidence: 99%
“…We then utilized plant lectins to target this post-translational modi cation and inhibit the ACE2-RBD interaction and demonstrated its potential as an antiviral using a pseudovirion system. A recent study demonstrated that it was viable to engineer a banana lectin to inhibit in uenza A virus infection in mice while minimizing mitogenic effects associated with lectins 29 . The most potent antiviral lectin identi ed in this study, ConA, may similarly act as a lead candidate to enable the development of a SARS-CoV-2 spike glycan-targeted lectin.…”
Section: Discussionmentioning
confidence: 99%